A remodelable elastomer composition and its preparation method

CN122941070APending Publication Date: 2026-10-20GUANGZHOU MEICUN RUBBER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611359404.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0002]弹性体因其高弹性广泛应用于密封、缓冲等工业领域,然而,传统弹性体通常依赖硫磺或过氧化物构建永久化学交联的三维网络,这种不可逆的共价结构虽然赋予了材料稳定的服役尺寸,但也导致其报废后无法通过熔融加工实现重塑再生,难以回收利用,最终形成大量难以降解的“黑色污染”

Benefits of technology

本发明制备的可重塑弹性体组合物由自制改性POSS-PEG交联剂与羧基丁腈橡胶、酯交换催化剂发生反应制备而成,形成以POSS为核,酯交换、氢键交联以及烷氧基胺可逆交联三级交联点位的稳定结构,同时与羧基化单壁碳纳米管反应,通过将补强剂接入交联体系,赋予更强的钉扎效应,提升整体力学性能,并在升温过程实现重塑再生、循环利用,经测试在温度140~160℃,压力6MPa下重塑3次,拉伸强度保持率大于95%,具体可塑性过程如下:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to the field of elastomers, specifically to a remodelable elastomer composition. The remodelable elastomer composition prepared by this invention is prepared by reacting a self-made modified POSS-PEG crosslinking agent with carboxylated butadiene-acrylonitrile rubber and an ester exchange catalyst, forming a stable structure with POSS as the core and tertiary crosslinking sites of ester exchange, hydrogen bonding, and reversible crosslinking of alkoxyamines. This endows the material with excellent mechanical properties and enables self-repair and remodeling during the heating process, realizing the regeneration and recycling of the elastomer. This invention constructs a multi-level crosslinking site and multi-layer structure to achieve crosslinking and decrosslinking at different temperatures, thereby endowing the rubber with thermally reversible repeated processing and reducing irreversible damage to the elastomer network structure through an ordered decrosslinking process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of elastomers, specifically to a remodelable elastomer composition. Background Technology

[0002] Elastomers are widely used in industrial fields such as sealing and cushioning due to their high elasticity. However, traditional elastomers usually rely on sulfur or peroxides to build a three-dimensional network of permanent chemical cross-linking. Although this irreversible covalent structure gives the material stable service dimensions, it also makes it impossible to reshape and regenerate it through melting after it is scrapped, making it difficult to recycle and ultimately forming a large amount of "black pollution" that is difficult to degrade.

[0003] To address the challenge of non-recyclability of thermosetting elastomers, existing technologies attempt to introduce physical blending systems or single dynamic crosslinking systems. Physical blending systems achieve remodeling and regeneration through melt blending of elastomers and plastic resins. In this system, the elastomer phase is separated and diluted by the plastic phase, resulting in significantly lower heat aging resistance and mechanical strength compared to traditional crosslinked elastomers. The phase interface relies solely on physical entanglement for maintenance, making it highly susceptible to stress relaxation and creep failure under continuous loads. On the other hand, single dynamic crosslinking systems struggle to balance stable network nodes at room temperature with dynamic exchange rates at high temperatures due to the difficulty of achieving this balance between these dynamic bonds. Consequently, they exhibit insufficient low-temperature strength and poor high-temperature fluidity.

[0004] Therefore, developing a novel elastomer composition that combines excellent mechanical properties with high remodelability, and constructing a more stable and efficient composite dynamic crosslinking network system, is of great significance for improving material service life, reducing total life cycle cost, alleviating the environmental pressure of waste elastomers, and promoting the sustainable development of special polymer materials. Summary of the Invention

[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a remodelable elastomer composition and its preparation method. The remodelable elastomer composition prepared by this method retains more than 95% of its tensile strength after being remodeled three times.

[0006] (II) Technical Solution A method for preparing a remodelable elastomer composition, which is prepared by a three-stage crosslinking reaction involving a modified POSS-PEG crosslinking agent, carboxylated butadiene-acrylonitrile rubber, and an ester exchange catalyst, including ester exchange, hydrogen bonding, and reversible crosslinking with alkoxyamines. The modified POSS-PEG crosslinking agent contains the following structural formula: ; Among them, R1~R8 contain reaction segments: terminal epoxy urea-based polyethylene glycol flexible segments and nitroxide free radical segments.

[0007] The modified POSS-PEG crosslinking agent prepared in this invention is modified to have different long and short chain segments, including terminal epoxy urea-based polyethylene glycol flexible chain segments and nitroxide free radical chain segments. The orderly tertiary crosslinking is achieved by arranging different crosslinking sites in the long and short chains, which reduces damage to the elastomer itself and the generation of defects in the subsequent reshaping process, thus achieving long-term use and reshaping.

[0008] At the long chain end of the modified POSS-PEG crosslinking agent, the epoxy at the end of the flexible polyethylene glycol segment reacts with the carboxyl group of the carboxylated acrylonitrile rubber. The epoxy ring opens to form ester bonds and hydroxyl groups, forming ester crosslinking sites. In addition, the urea groups on the long chain form hydrogen bonds for crosslinking. At the same time, the carbon-carbon double bonds on the carboxylated acrylonitrile rubber molecular chain are unstable and homolytically cleaved when heated to 150~160℃, forming unstable carbon center free radicals. The nitroxide free radicals at the short chain end quickly capture these unstable carbon free radicals and form C-ON bond crosslinking sites through alkoxyamine reaction, thereby realizing a tertiary crosslinking network.

[0009] Furthermore, the process also includes adding carboxylated single-walled carbon nanotubes, stearic acid, and solvent to the reaction solution of the modified POSS-PEG crosslinking agent, carboxylated butadiene-acrylonitrile rubber, and transesterification catalyst. After stirring evenly, the mixture is poured into a rubber mold, the solvent is removed in a vacuum oven at 90~100℃, and the mixture is pre-cured at 120~140℃ for 1~2 hours and cured at 150~160℃ for 2~4 hours to obtain a remodelable elastomer composition.

[0010] Carboxylated single-walled carbon nanotubes serve as reinforcing agents. Through the epoxy reaction of carboxyl groups with modified POSS-PEG crosslinking agents, they are integrated into a dynamic crosslinking network. This not only prevents the reinforcing agent from shifting and precipitating over time, but also works synergistically with the crosslinking network to form a more stable pinning effect. Furthermore, the reinforcing agents self-repair during the remodeling process, thereby improving the overall mechanical properties.

[0011] Furthermore, the solvent may be one or a mixture of toluene, isopropanol, and N,N-dimethylformamide, and the mass of the solvent is 50% of the mass of the carboxylated nitrile rubber.

[0012] Furthermore, the reaction also includes the step of adding an antioxidant to the reaction solution. For 100 parts of carboxylated acrylonitrile rubber, the antioxidant is 1 to 1.5 parts, the carboxylated single-walled carbon nanotubes are 3 to 6 parts, and the stearic acid is 0.5 to 1 part.

[0013] Furthermore, the transesterification catalyst comprises at least one of zinc acetylacetonate, chromium acetylacetonate, and zinc acetate.

[0014] Furthermore, the antioxidant comprises at least one of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and 2,6-di-tert-butyl-4-methylphenol.

[0015] Furthermore, the preparation method of the modified POSS-PEG crosslinking agent specifically includes the following steps: Step 1: Under a nitrogen atmosphere, add diamino-terminated polyethylene glycol to a flask, add 3-isocyanate-propylmethyltrimethoxysilane and dibutyltin dilaurate, and heat to 70-80℃ and react for 1-2 hours. After the reaction is completed, wash and dry to obtain intermediate 1. Step 2: Add intermediate 1, 1,4-bis(ethylene oxide-2-yl)benzene and toluene solvent to a flask, heat to 60~70℃ and react for 4~6 hours. After the reaction is completed, distill under reduced pressure to obtain intermediate 2. Step 3: Under a nitrogen atmosphere, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical and toluene solvent were added to a flask, followed by the addition of 3-isocyanate-propylmethyltrimethoxysilane and dibutyltin dilaurate. The mixture was heated to 80-90°C and reacted for 6-8 hours. After the reaction was completed, the mixture was purified and dried to obtain intermediate 3. Step 4: Place isopropanol solvent and tetramethylammonium hydroxide solution in a flask, then place intermediate 2, intermediate 3, methyltrimethoxysilane and toluene solvent in a constant pressure funnel, stir well and add to the flask, react at 20~30℃ for 6~8h, then raise the temperature to 70~80℃ and react for 2~4h. After the reaction is completed, obtain the modified POSS-PEG crosslinking agent by vacuum distillation and washing.

[0016] Furthermore, in step 1, the mass ratio of diamino-terminated polyethylene glycol, 3-isocyanate-based propylmethyltrimethoxysilane, and dibutyltin dilaurate is 1:0.16~0.20:0.002~0.003.

[0017] Furthermore, the molecular weight of the diamino-terminated polyethylene glycol is 500-1000.

[0018] Furthermore, in step 2, the mass ratio of intermediate 1 to 1,4-bis(ethylene oxide-2-yl)benzene is 1:0.14~0.16.

[0019] Furthermore, in step 2, the mass of toluene solvent is 30% to 50% of the mass of intermediate 1.

[0020] Furthermore, in step 3, the mass ratio of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical, 3-isocyanate-propylmethyltrimethoxysilane, and dibutyltin dilaurate is 1:1.16~1.27:0.007~0.01.

[0021] Furthermore, in step 3, the mass of the toluene solvent is 60% to 90% of the mass of the 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical.

[0022] Furthermore, in step 4, the mass ratio of intermediate 2, intermediate 3, methyltrimethoxysilane, and tetramethylammonium hydroxide solution is 1:0.27~0.33:0.18~0.20:0.03~0.04, wherein the tetramethylammonium hydroxide solution is a 25wt% tetramethylammonium hydroxide methanol solution.

[0023] This invention controls the ratio of intermediate 2, intermediate 3, and methyltrimethoxysilane to make the modified POSS-PEG crosslinking agent have a POSS cage-like polyhedron as the core. The eight vertices R1 to R8 groups of the POSS cage fall within the statistical range of m grafted with terminal epoxy urea-based polyethylene glycol flexible long chain segments and n grafted with nitrile free radical short chain segments, where m+n=2~8 and m:n=1:3~3:1.

[0024] Furthermore, in step 4, the isopropanol solvent is 100% of the total mass of the reaction monomers (intermediate 2, intermediate 3, methyltrimethoxysilane), and the toluene solvent is 50% of the mass of the isopropanol solvent.

[0025] A remodelable elastomer composition, prepared by any one of the above preparation methods, characterized in that it comprises the following components in parts by weight: 100 parts of carboxylated nitrile rubber, 8-15 parts of modified POSS-PEG crosslinking agent, and 1-2 parts of transesterification catalyst.

[0026] Beneficial technical effects The remodelable elastomer composition prepared in this invention is produced by reacting a self-made modified POSS-PEG crosslinking agent with carboxylated butadiene-acrylonitrile rubber and an ester exchange catalyst to form a stable structure with POSS as the core and tertiary crosslinking sites of ester exchange, hydrogen bonding, and reversible alkoxyamine crosslinking. Simultaneously, it reacts with carboxylated single-walled carbon nanotubes. By incorporating a reinforcing agent into the crosslinking system, a stronger pinning effect is imparted, improving the overall mechanical properties. Furthermore, it achieves remodeling, regeneration, and recycling during the heating process. Testing showed that after three remodeling cycles at 140-160℃ and 6MPa, the tensile strength retention rate was greater than 95%. The specific plasticity process is as follows: During the heating process, the hydrogen bonds in the remodelable elastomer composition unwind first, eliminating some defects caused by use. With further heating, the hydroxyl groups attack the peripheral long-chain ester bonds, generating new hydroxyl groups and new ester bonds, achieving topological rearrangement of the crosslinking network. After the periphery completes the plastic transformation step by step, the carbon-oxygen bonds in the NO-C of the short-chain alkoxyamine break, generating new carbon free radicals and nitrile free radicals. At this point, the rubber undergoes decrosslinking and can be remodeled. When the temperature cools down, the nitrile free radicals quickly combine with the carbon free radicals to form an alkoxyamine structure. The activity of the hydroxyl groups decreases, the ester groups remain stably crosslinked, and hydrogen bonds are reformed.

[0027] In this invention, the POSS cage-like core serves as the central anchor point of the entire tertiary crosslinking network. Its rigid Si-O-Si bond energy of 452 kJ / mol is higher than that of the C-C bond of the main body of nitrile rubber (348 kJ / mol), which enables the POSS cage-like core to maintain structural integrity during the reshaping process and provides a spatial positioning reference for the dynamic crosslinking and decrosslinking processes of long and short chains.

[0028] Specifically, combined with dynamic mechanical analysis of the temperature-loss angle Tanδ under DMA (-40~200℃, 1Hz), it can be seen that when the temperature rises to about 80℃, the hydrogen bonds at the long chain ends extending outward from the POSS core dissociate, eliminating surface defects; with further heating to about 120℃, the ester bonds at the long chain ends undergo dynamic exchange, realizing network topology rearrangement; finally, with heating to about 150℃, the alkoxyamines at the short chain ends dissociate, and the rubber matrix decrosslinks and enters a remodelable state. At the same time, due to the anchoring effect of the POSS core, even when the alkoxyamines dissociate at the highest temperature, the POSS core still maintains a locally ordered structure, preventing the network from completely collapsing into a disordered melt. Thus, after cooling, it can quickly restore an ordered multi-level crosslinked state, which is the key mechanism for the tensile strength retention rate of >95% after three remodeling cycles.

[0029] This invention uses the POSS core rule as an anchor point to firmly stabilize the entire system, uses temperature as a switch for crosslinking and decrosslinking, and uses long and short chains to control their arrangement position according to different switches, thereby giving the rubber thermal reversible repeatable processing, reducing irreversible damage to the elastomer network structure under the combination of temperature order and position order. Attached Figure Description

[0030] Figure 1 The temperature-loss angle Tanδ relationship is shown for Embodiment 4 and Comparative Examples 1-7 of the present invention under dynamic mechanical analysis DMA (-40~200℃, 1Hz). Detailed Implementation

[0031] The following provides a detailed description of specific embodiments of the present invention. Unless otherwise specified, the materials and reagents used in the specific embodiments described herein are commercially available. Experimental methods not specified in the examples are generally performed under conventional conditions or as recommended by the manufacturer.

[0032] The tetramethylammonium hydroxide solution used below is a 25wt% tetramethylammonium hydroxide methanol solution.

[0033] Examples 1-3 are preferred methods for preparing modified POSS-PEG crosslinking agents.

[0034] Example 1 Step 1: Under a nitrogen atmosphere, 20g of diamino-terminated polyethylene glycol (molecular weight 1000) was added to a flask, followed by 3.2g of 3-isocyanatopropylmethyltrimethoxysilane and 0.04g of dibutyltin dilaurate. The mixture was heated to 70℃ and reacted for 2 hours. After the reaction was completed, the mixture was washed and dried to obtain intermediate 1 with a yield of approximately 81%. The characterization results of intermediate 1 are as follows: Fourier transform infrared spectroscopy (FT-IR) (KBr) test / cm -1 :3443(m,sh,νN-H), 3350(m,br,νN-H),2918(s,νasCH2),2846(s,νsCH2+νO-CH3,),1655(νs,νC=O),1572(m,δN-H+νC-N),1465(m,δCH2),1420(w, νC-N),1191(m,δSi-O-CH3),1108(νs,br,νasC-O-C+νSi-OC),1047(m,νSi-OC),952(w,νsC-OC),818(w,νSi-O),722(w,ρCH2); Nuclear magnetic resonance spectrometer (NMR) 1 ¹H NMR (CDCl₃, 400MHz) test / ppm: δ 6.50 (brs, 2H), 3.66~3.52 (m, 24H), 3.55 (s, 9H), 3.15~3.01 (m, 6H), 1.91 (brs, 2H), 1.51 (m, 2H), 0.56 (t, 2H).

[0035] Based on the FT-IR characterization results, 1655cm -1 A strong absorption peak appears at 3350 cm⁻¹, attributed to the stretching vibration of the urea carbonyl group. This wavenumber is lower than that of ordinary amides, indicating that the carbonyl group is affected by the electron-donating effect of two adjacent amino groups. Simultaneously, a strong absorption peak appears at 3350 cm⁻¹. -1 A broadened NH stretching vibration peak was observed at 1572 cm⁻¹. -1The NH bending and CN stretching coupling vibrations at the molecule jointly confirm the presence of a urea group. This urea group connects the silane and polyethylene glycol-amino segments, and the amino group is successfully grafted onto the silane segment. 1 ¹H NMR characterization showed that δ 6.50 ppm is typical for the chemical shift range of the NH proton in urea compounds, and the broad peak at δ 1.91 ppm is attributed to the terminal –NH₂, indicating that intermediate 1 was successfully synthesized.

[0036] Step 2: 10g of intermediate 1, 1.4g of 1,4-bis(ethylene oxide-2-yl)benzene, and 3g of toluene solvent were added to a flask, and the mixture was heated to 60℃ and reacted for 6 hours. After the reaction was completed, the mixture was distilled under reduced pressure to obtain intermediate 2, with a yield of approximately 77%. The characterization results of intermediate 2 are as follows: Fourier transform infrared spectroscopy (FT-IR) (KBr) test / cm -1 :3405(br,s,νO-H), 3350(br,m,νN-H),3300(m,νN-H),2925(s,νasCH2),2855(s,νsCH2),2838( m,νO-CH3),1655(νs,νC=O),1570(m,δN-H+νC-N),1466(m,δCH2),1419(w,νC -N),1188(m,δSi-O-CH3),1110(νs,br,νasC-O-C+νSi-OC),1060(m,νC-O),1 020(m,νSi-OC),910(w,γC-OC),834(m,γC-H),816(w,νSi-O),725(w,ρCH2); Nuclear magnetic resonance spectrometer (NMR) 1 ¹H NMR (CDCl₃, 400MHz) test / ppm: δ 7.28 (m, 3H), 6.50 (brs, 2H), 5.20 (t, 1H), 4.87 (s, 2H), 3.83 (m, 1H), 3.66 (t, 2H), 3.55 (s, 9H), 3.52 (m, 20H), 3.15~2.71 (m, 8H), 2.30 (s, 1H), 1.51 (m, 2H), 0.56 (t, 2H).

[0037] Based on the FT-IR characterization results, 3405 cm -1 A broad and strong OH stretching vibration peak appears at 1655 cm⁻¹. -1 The urea C=O peak was retained, as well as the 910 cm⁻¹ peak. -1 The characteristic peaks of the epoxy groups still exist, combined with 1The presence of a methylene signal around δ3.83 ppm and an epoxy signal from δ3.15 to 2.71 ppm in the HNMR indicates that step 2 proceeded as expected, successfully introducing the phenyl epoxy structure to the end of the molecule, while the urea-polyethylene glycol-silyl group was basically retained.

[0038] Step 3: Under a nitrogen atmosphere, 10g of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical and 6g of toluene solvent were added to a flask. Then, 11.6g of 3-isocyanopropylmethyltrimethoxysilane and 0.07g of dibutyltin dilaurate were added, and the mixture was heated to 80℃ and reacted for 8 hours. After the reaction was completed, the mixture was purified and dried to obtain intermediate 3 with a yield of approximately 85%. The characterization results of intermediate 3 are as follows: Fourier transform infrared spectroscopy (FT-IR) (KBr) test / cm -1 :3342(br,m,νN-H), 2968(s,νC-H),2838(m,νO-CH3),1735(νs,νC=O,),1465(m,δCH2),1380(m,δsCH3),1365(m,δsCH3),1360(m,νN-O•),1247(s,νasC- O-C+νC-N),1190(m,δSi-O-CH3),1110(νs,br,νasC-O-C+νSi-OC),1080(m,νsC-OC),1018(m,νSi-OC),820(w,νSi-O),720(w,ρCH2); Nuclear magnetic resonance spectrometer (NMR) 1 ¹H NMR (CDCl₃, 400MHz) test / ppm: δ 7.50 (brs, 1H), 5.22 (m, 1H), 3.55 (s, 9H), 3.18 (m, 2H), 1.76 (m, 2H), 1.51 (m, 4H), 1.22 (s, 12H), 0.56 (t, 2H).

[0039] Based on the FT-IR characterization results, 1735cm -1 A strong absorption peak appears at 3342 cm⁻¹, attributed to the stretching vibration (νC=O) of the urethane carbonyl group. This peak position is shifted to a higher wavenumber than that of the urea carbonyl group. -1 It is an NH stretching vibration, 1360cm -1 A moderate intensity peak appears at this point, which is attributed to the NO• stretching vibration of the TEMPO radical. 1 HNMR characterization showed that δ1.22 ppm was assigned to the methyl proton of the piperidine ring, and δ1.76 ppm and δ1.51 ppm were assigned to the remaining methylene protons of the piperidine ring, indicating that the TEMPO structure was successfully introduced into the molecule terminus.

[0040] Step 4: Place 14.5g of isopropanol solvent and 0.3g of tetramethylammonium hydroxide solution in a flask. Then, place 10g of intermediate 2, 2.7g of intermediate 3, 1.8g of methyltrimethoxysilane, and 7.25g of toluene solvent in a constant pressure funnel, stir well, and add to the flask. React at 20℃ for 8 hours, then raise the temperature to 70℃ and react for 4 hours. After the reaction is complete, distill under reduced pressure and wash to obtain the modified POSS-PEG crosslinking agent, with a yield of approximately 74%. The characterization results of the modified POSS-PEG crosslinking agent are as follows: Fourier transform infrared spectroscopy (FT-IR) (KBr) test / cm -1 :3400(br,m,νO-H+νN-H), 2951(s,νC-H),2925(s,νasCH2,PEG),2855(s,νsCH2,PEG),1735(νs,νC=O),1655( s,νC=O),1572(m,δN-H+νC-N),1465(m,δCH2),1380(m,δsCH3),1365(m,δsCH3),135 9(m,νN-O•),1250(s,νasC-OC),1110(νs,br,νasSi-O-Si+νasC-OC),1080(m,νC-O) ,1060(m,νC-O),910(w,γC-OC),850(m,νSi-C),800(νs,νsSi-O-Si),725(w,ρCH2); Nuclear magnetic resonance spectrometer (NMR) 1 HNMR) (CDCl3, 400MHz) test / ppm: δ7.50 (br, s, 2H), 7.28(m,8H),6.50(br,s,4H),5.22(m,2H),5.20(t,2H),4.87(m,2H),3.83(m,2H),3.66(t,4H),3.52 (m),3.40(m,4H),3.18~3.01(m,8H),2.72(t,4H),2.30(br,s,2H),1.76~1.51(m,8H),1.22(s,12H), 1.14(s,12H),0.84~0.56(m,8H).

[0041] Based on the FT-IR characterization results, 1110cm -1 An extremely broad and strong absorption peak appears at 800 cm⁻¹. -1 Extremely strong peaks appear at 850 cm⁻¹, which are attributed to the asymmetric and symmetric stretching vibrations of the POSS cage Si-O-Si framework, respectively. -1 The appearance of a moderate-intensity spike at this point is attributed to the stretching vibrations of the Si-C bonds in the POSS cage. Both of these factors jointly confirm the formation of the POSS cage structure.1 HNMR characterization showed that δ 5.2 ppm was attributed to the siloxane-linked methylene proton, indicating that the trimethoxysilyl group has been successfully converted into a POSS cage structure.

[0042] Example 2 Step 1: Under a nitrogen atmosphere, 20g of diamino-terminated polyethylene glycol (molecular weight 800) was added to a flask, along with 3.6g of 3-isocyanate-propylmethyltrimethoxysilane and 0.05g of dibutyltin dilaurate. The mixture was heated to 75°C and reacted for 1.5h. After the reaction was completed, the mixture was washed and dried to obtain intermediate 1. Step 2: Add 10g of intermediate 1, 1.5g of 1,4-bis(ethylene oxide-2-yl)benzene and 4g of toluene solvent to a flask, heat to 65℃ and react for 5h. After the reaction is completed, distill under reduced pressure to obtain intermediate 2. Step 3: Under a nitrogen atmosphere, 10g of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical and 8g of toluene solvent were added to a flask. Then, 12.1g of 3-isocyanate-propylmethyltrimethoxysilane and 0.08g of dibutyltin dilaurate were added. The temperature was raised to 85℃ and the reaction was carried out for 7 hours. After the reaction was completed, the product was purified and dried to obtain intermediate 3. Step 4: Place 14.9g of isopropanol solvent and 0.35g of tetramethylammonium hydroxide solution in a flask. Then, place 10g of intermediate 2, 3g of intermediate 3, 1.9g of methyltrimethoxysilane and 7.45g of toluene solvent in a constant pressure funnel, stir well and add to the flask. React at 25℃ for 7h, then raise the temperature to 75℃ and react for 3h. After the reaction is completed, obtain the modified POSS-PEG crosslinking agent by vacuum distillation and washing.

[0043] Example 3 Step 1: Under a nitrogen atmosphere, 20g of diamino-terminated polyethylene glycol (molecular weight 500) was added to a flask, and 4g of 3-isocyanate-propylmethyltrimethoxysilane and 0.06g of dibutyltin dilaurate were added. The temperature was raised to 80℃ and reacted for 1h. After the reaction was completed, the product was washed and dried to obtain intermediate 1. Step 2: Add 10g of intermediate 1, 1.6g of 1,4-bis(ethylene oxide-2-yl)benzene and 5g of toluene solvent to a flask, heat to 70℃ and react for 4h. After the reaction is completed, distill under reduced pressure to obtain intermediate 2. Step 3: Under a nitrogen atmosphere, 10g of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical and 9g of toluene solvent were added to a flask. Then, 12.7g of 3-isocyanate-propylmethyltrimethoxysilane and 0.1g of dibutyltin dilaurate were added. The temperature was raised to 90℃ and the reaction was carried out for 6 hours. After the reaction was completed, the product was purified and dried to obtain intermediate 3. Step 4: Take 15.3g of isopropanol solvent and 0.4g of tetramethylammonium hydroxide solution and place them in a flask. Then take 10g of intermediate 2, 3.3g of intermediate 3, 2g of methyltrimethoxysilane and 7.65g of toluene solvent in a constant pressure funnel, stir well and add them to the flask. React at 30℃ for 6h, then raise the temperature to 80℃ and react for 2h. After the reaction is completed, obtain the modified POSS-PEG crosslinking agent by vacuum distillation and washing.

[0044] The following are examples and comparative examples for preparing remodelable elastomer compositions: Example 4 Step 1: Mix 10g of carboxylated nitrile rubber, 0.8g of the modified POSS-PEG crosslinking agent obtained in Example 1, and 0.1g of chromium acetylacetone to prepare a reaction solution. After stirring evenly, pour the solution into a rubber mold, remove the solvent in a vacuum oven at 90℃, pre-cur at 120℃ for 2 hours, and then cure at 150℃ for 4 hours to obtain a remodelable elastomer composition. The following characterization is based on the obtained remodelable elastomer composition: Fourier transform infrared spectroscopy (FT-IR) (KBr) test / cm -1 :2237(s,sharp,νC≡N),3300(s,br,νN-H+νO-H),1737(s,νC=O),1642(s,νC=O),1558(s,δN-H+νC-N),1360(w,νN-O),1240(s,ν as COC),1100(νs,br,νSi-O-Si+νC-OC); Swelling test (the remodelable elastomer composition sample was immersed in toluene at room temperature for 48 hours): swelling rate 12%.

[0045] Based on the FT-IR characterization results, at 1737 cm⁻¹ -1 A stretching vibration peak of the ester bond C=O was observed at 1642 cm⁻¹. -1 A urea group NH bending vibration peak was observed at 1360 cm⁻¹. -1 The NO stretching vibration peak of TEMPO was observed, confirming the formation of the tertiary cross-linked network, and the swelling experiment also proved the existence of the cross-linked network.

[0046] Example 5 Step 1: Mix 10g of carboxylated acrylonitrile rubber, 0.8g of the modified POSS-PEG crosslinking agent obtained in Example 1, 0.1g of zinc acetylacetonate, 0.3g of carboxylated single-walled carbon nanotubes, 0.05g of stearic acid and 5g of toluene solvent to prepare a reaction solution. After stirring evenly, pour the solution into a rubber mold, remove the solvent in a vacuum oven at 90°C, pre-cur at 120°C for 2 hours, and cure at 150°C for 4 hours to obtain a remodelable elastomer composition.

[0047] Example 6 10g of carboxylated acrylonitrile rubber, 0.8g of the modified POSS-PEG crosslinking agent obtained in Example 1, 0.1g of zinc acetylacetonate, 0.3g of carboxylated single-walled carbon nanotubes, 0.05g of stearic acid, 5g of isopropanol solvent, and 0.1g of 2,2,4-trimethyl-1,2-dihydroquinoline polymer were mixed to prepare a reaction solution. After stirring evenly, the solution was poured into a rubber mold, and the solvent was removed in a vacuum oven at 90°C. The solution was then pre-cured at 120°C for 2 hours and cured at 150°C for 4 hours to obtain a remodelable elastomer composition.

[0048] Example 7 10g of carboxylated acrylonitrile rubber, 1.1g of the modified POSS-PEG crosslinking agent obtained in Example 1, 0.15g of zinc acetylacetonate, 0.4g of carboxylated single-walled carbon nanotubes, 0.08g of stearic acid, 5g of isopropanol solvent, and 0.12g of 2,2,4-trimethyl-1,2-dihydroquinoline polymer were mixed to prepare a reaction solution. After stirring evenly, the solution was poured into a rubber mold, and the solvent was removed in a vacuum oven at 95°C. The solution was pre-cured at 130°C for 1.5h and then cured at 155°C for 3h to obtain a remodelable elastomer composition.

[0049] Example 8 10g of carboxylated acrylonitrile rubber, 1.5g of the modified POSS-PEG crosslinking agent obtained in Example 1, 0.2g of zinc acetylacetone, 0.6g of carboxylated single-walled carbon nanotubes, 0.1g of stearic acid, 5g of isopropanol solvent, and 0.15g of 2,2,4-trimethyl-1,2-dihydroquinoline polymer were mixed to prepare a reaction solution. After stirring evenly, the solution was poured into a rubber mold, and the solvent was removed in a vacuum oven at 100°C. The solution was then pre-cured at 140°C for 1 hour and cured at 160°C for 2 hours to obtain a remodelable elastomer composition.

[0050] Comparative Example 1 The difference between Comparative Example 1 and Example 4 is that in step 3 of the modified POSS-PEG crosslinking agent used in Example 1, glycidol is used instead of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy free radical, while the remaining steps are roughly the same as in Example 4.

[0051] Comparative Example 2 The difference between Comparative Example 2 and Example 4 is that in the modified POSS-PEG crosslinking agent used in Example 1, glycidol was used instead of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical in step 3, and intermediate 2 was not added in step 4. The remaining steps are roughly the same as in Example 4.

[0052] Comparative Example 3 The difference between Comparative Example 3 and Example 4 is that intermediate 2 is not added in step 4 of the modified POSS-PEG crosslinking agent used in Example 1, while the remaining steps are roughly the same as in Example 4.

[0053] Comparative Example 4 The difference between Comparative Example 4 and Example 4 is that intermediate 3 is not added in step 4 of the modified POSS-PEG crosslinking agent used in Example 1, while the remaining steps are roughly the same as in Example 4.

[0054] Comparative Example 5 The difference between Comparative Example 5 and Example 4 is that in the modified POSS-PEG crosslinking agent of Example 1 used in Example 1, intermediate 1 was added in step 4 instead of intermediate 2, while the remaining steps were roughly the same as in Example 4.

[0055] Comparative Example 6 The difference between Comparative Example 6 and Example 4 is that methyl-(3-isocyanate propyl)dimethylsilane is used instead of 3-isocyanate propyl methyltrimethoxysilane in Examples 1 and 3, while the remaining steps are roughly the same as in Example 4.

[0056] Comparative Example 7 The difference between Comparative Example 7 and Example 6 is that ordinary single-walled carbon nanotubes are used instead of carboxylated single-walled carbon nanotubes, while the remaining steps are roughly the same as in Example 6.

[0057] Remodeling process test method: The elastomer compositions prepared in Examples 4-8 and Comparative Examples 1-7 were chopped into powder and hot-pressed for 4 hours at 6 MPa pressure and 140°C or 160°C using a hydraulic flat vulcanizing machine to obtain samples with different reprocessing times. Tensile strength tests were then performed at room temperature according to GB / T1040.2-2006.

[0058] Dynamic mechanical analysis test (DMA): Samples from Example 4 and Comparative Examples 1 to 7 were placed in a dynamic mechanical analyzer and tested under conditions of -40 to 200°C and 1 Hz.

[0059] The test results are as follows:

[0060]

[0061] Figure 1 The temperature-loss angle Tanδ relationship of Embodiment 4 and Comparative Examples 1-7 of the present invention under dynamic mechanical analysis DMA (-40~200℃, 1Hz).

[0062] Based on the tensile strength and its retention rate, after reshaping three times at a temperature of 140~160℃ and a pressure of 6MPa, the tensile strength retention rate is greater than 95%.

[0063] Combined with Tables 1-2, Figure 1 Specific embodiments and comparative examples analysis: The difference between Comparative Example 1 and Example 4 is that the reversible crosslinking of alkoxyamines is replaced with ester crosslinking, resulting in only secondary crosslinking. Both long and short chains are ester crosslinked simultaneously, making it difficult to utilize spatial dislocations and different crosslinking mechanisms. In dealing with the dynamic remodeling process of crosslinking and decrosslinking, a significant decrease in retention rate is observed. Figure 1 It can also be seen that there are only two peaks. Compared with the situation in Example 4, it can be further inferred that the peak at 150°C is the process of reversible crosslinking and decrosslinking of alkoxyamine. It can also be seen that the peak at 120°C is significantly increased. Combined with the replacement of reversible crosslinking of alkoxyamine with ester crosslinking, it can be inferred that 120°C is the process of ester crosslinking and decrosslinking, and the remaining peak at 80°C is the process of hydrogen bond crosslinking and decrosslinking.

[0064] Comparative Examples 2-5 examine the differences between single-stage and two-stage crosslinking and the three-stage crosslinking of Example 4 from another perspective. Comparative Example 2 contains only transesterification, and Comparative Example 3 contains only reversible crosslinking with alkoxyamines. The tensile strength retention rate was below 95% in the first reshaping. It is speculated that during the reshaping process, direct dissociation easily causes excessive local stress and chaotic stacking, leading to a rapid decrease in tensile strength after multiple reshapings. Comparative Example 4 contains only transesterification and hydrogen bond crosslinking, and Comparative Example 5 contains only reversible crosslinking with alkoxyamines and hydrogen bond crosslinking, increasing the hydrogen bond dissociation buffer and showing a preliminary improvement effect. Figure 1 It can also be observed that comparative examples 2 and 3 only have a single peak, while comparative examples 4 and 5 show a small peak at 80℃.

[0065] Comparative Example 6 replaced 3-isocyanopropylmethyltrimethoxysilane with methyl-(3-isocyanate-propyl)dimethylsilane. The dimethoxy group prevented the formation of POSS cores during the crosslinking agent synthesis process. After three remodelings, the retention rate dropped rapidly, indicating that POSS cores play a role in maintaining the local ordered structure and preventing the network from completely collapsing into a disordered melt.

[0066] Compared with Example 6, Comparative Example 7 showed a decrease in both tensile strength and retention. It is speculated that when ordinary single-walled carbon nanotubes are used as reinforcing agents, they are isolated outside the cross-linking system and fail to work well with the dynamic cross-linking network, thus failing to achieve a synergistic improvement in tensile strength.

[0067] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a remodelable elastomer composition, characterized in that, It was prepared by a three-stage crosslinking reaction involving modified POSS-PEG crosslinking agent, carboxylated butadiene-acrylonitrile rubber, and transesterification catalyst, including transesterification, hydrogen bonding, and reversible crosslinking with alkoxyamine. The modified POSS-PEG crosslinking agent contains the following structural formula: ; Among them, R1~R8 contain reaction segments: terminal epoxy urea-based polyethylene glycol flexible segments and nitroxide free radical segments.

2. The preparation method according to claim 1, characterized in that, The method also includes adding carboxylated single-walled carbon nanotubes, stearic acid, and solvent to the reaction solution of the modified POSS-PEG crosslinking agent, carboxylated butadiene-acrylonitrile rubber, and transesterification catalyst. After stirring evenly, the mixture is poured into a rubber mold, the solvent is removed in a vacuum oven at 90~100℃, and the mixture is pre-cured at 120~140℃ for 1~2 hours and cured at 150~160℃ for 2~4 hours to obtain a remodelable elastomer composition.

3. The preparation method according to claim 2, characterized in that, It also includes the step of adding antioxidants to the reaction solution. Calculated based on 100 parts of carboxylated acrylonitrile rubber, the antioxidant is 1-1.5 parts, the carboxylated single-walled carbon nanotubes are 3-6 parts, and the stearic acid is 0.5-1 parts.

4. The preparation method according to claim 3, characterized in that, The transesterification catalyst comprises at least one of zinc acetylacetonate, chromium acetylacetonate, and zinc acetate, and the antioxidant comprises at least one of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, and 2,6-di-tert-butyl-4-methylphenol.

5. The preparation method according to claim 1, characterized in that, The preparation method of the modified POSS-PEG crosslinking agent specifically includes the following steps: Step 1: Under a nitrogen atmosphere, diamino-terminated polyethylene glycol was added to a flask, followed by the addition of 3-isocyanate-propylmethyltrimethoxysilane and dibutyltin dilaurate. The temperature was raised to 70-80°C and the reaction was carried out for 1-2 hours. After the reaction was completed, the product was washed and dried to obtain intermediate 1. The specific reaction is as follows: ; Step 2: Add intermediate 1, 1,4-bis(ethylene oxide-2-yl)benzene, and toluene solvent to a flask, heat to 60-70℃ and react for 4-6 hours. After the reaction is complete, distill under reduced pressure to obtain intermediate 2. The specific reaction is as follows: ; Step 3: Under a nitrogen atmosphere, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical and toluene solvent were added to a flask. Then, 3-isocyanatopropylmethyltrimethoxysilane and dibutyltin dilaurate were added, and the mixture was heated to 80-90℃ and reacted for 6-8 hours. After the reaction was completed, the mixture was purified and dried to obtain intermediate 3. The specific reaction is as follows: ; Step 4: Place isopropanol solvent and tetramethylammonium hydroxide solution in a flask, then place intermediate 2, intermediate 3, methyltrimethoxysilane and toluene solvent in a constant pressure funnel, stir well and add to the flask, react at 20~30℃ for 6~8h, then raise the temperature to 70~80℃ and react for 2~4h. After the reaction is completed, obtain the modified POSS-PEG crosslinking agent by vacuum distillation and washing.

6. The preparation method according to claim 5, characterized in that, In step 1, the mass ratio of diamino-terminated polyethylene glycol, 3-isocyanate-propylmethyltrimethoxysilane, and dibutyltin dilaurate is 1:0.16~0.20:0.002~0.003, and the molecular weight of the diamino-terminated polyethylene glycol is 500~1000.

7. The preparation method according to claim 5, characterized in that, In step 2, the mass ratio of intermediate 1 to 1,4-bis(ethylene oxide-2-yl)benzene is 1:0.14~0.

16.

8. The preparation method according to claim 5, characterized in that, In step 3, the mass ratio of 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy radical, 3-isocyanate-propylmethyltrimethoxysilane, and dibutyltin dilaurate is 1:1.16~1.27:0.007~0.

01.

9. The preparation method according to claim 5, characterized in that, In step 4, the mass ratio of intermediate 2, intermediate 3, methyltrimethoxysilane, and tetramethylammonium hydroxide solution is 1:0.27~0.33:0.18~0.20:0.03~0.04, wherein the tetramethylammonium hydroxide solution is a 25wt% tetramethylammonium hydroxide methanol solution.

10. A remodelable elastomer composition, prepared by the method according to any one of claims 1 to 9, characterized in that, The composition by weight includes the following components: 100 parts of carboxylated nitrile rubber, 8-15 parts of modified POSS-PEG crosslinking agent, and 1-2 parts of transesterification catalyst.